2002
DOI: 10.1056/nejmoa013474
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Implantation of a Defibrillator in Patients with Myocardial Infarction and Reduced Ejection Fraction

Abstract: In patients with a prior myocardial infarction and advanced left ventricular dysfunction, prophylactic implantation of a defibrillator improves survival and should be considered as a recommended therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

77
3,766
24
167

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 6,144 publications
(4,126 citation statements)
references
References 13 publications
77
3,766
24
167
Order By: Relevance
“…Although an association of both GDF‐15 and sST2 with sudden cardiac death was previously demonstrated, non‐ischaemic DCM represented one‐third to one‐half of these cohorts 24, 25, 37. Because of different aetiologies of the disease leading to different risks of AD,5, 8 it is of paramount importance to separately investigate ischaemic and non‐ischaemic heart failure patients. In addition, previous studies used sudden cardiac death as an end‐point, which is not always equivalent to fatal ventricular arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an association of both GDF‐15 and sST2 with sudden cardiac death was previously demonstrated, non‐ischaemic DCM represented one‐third to one‐half of these cohorts 24, 25, 37. Because of different aetiologies of the disease leading to different risks of AD,5, 8 it is of paramount importance to separately investigate ischaemic and non‐ischaemic heart failure patients. In addition, previous studies used sudden cardiac death as an end‐point, which is not always equivalent to fatal ventricular arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines for primary prevention with implantable cardioverter defibrillators (ICD) are based on the degree of LV ejection fraction (LVEF ≤ 30%‐40%) reduction 3, 4. However, patients with ischaemic heart disease seem to have more benefit from prophylactic ICD implantation 5, 6, 7. Furthermore, the recently published DANISH trial has demonstrated no mortality benefit from prophylactic ICD implantation in non‐ischaemic DCM 8.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there have been remarkable technical advances. The ICD is now widely used in high‐risk patients based on evidence from RCTs that supports the use of ICDs for both primary and secondary prevention of SCA 30, 31, 32, 33, 34, 35. In particular, 3 randomized controlled trials evaluated the impact of ICD therapy for secondary prevention indications (Table 1).…”
Section: Randomized Controlled Trials Of Icds and Guidelinesmentioning
confidence: 99%
“…The AVID 110 , CIDS 111 and CASH 112 trials established that ICD improved survival compared with antiarrhythmic agents for secondary prevention of sudden cardiac death (SCD). Other randomised, multicentre studies including MADIT I 19 and II 113 , MUSTT 114 and the SCD‐HeFT 115 , established ICD therapy as effective for primary prevention of SCD in selected patient populations. The LVEF cut offs used in these trials were < 40% in MUSTT, < 35% in MADIT I and SCD‐HeFT and < 30% in MADIT II.…”
Section: Role Of Echocardiography In Therapeutic Interventionmentioning
confidence: 99%